2019
DOI: 10.1186/s12885-019-5925-5
|View full text |Cite
|
Sign up to set email alerts
|

NR2F1 contributes to cancer cell dormancy, invasion and metastasis of salivary adenoid cystic carcinoma by activating CXCL12/CXCR4 pathway

Abstract: Background Salivary adenoid cystic carcinoma (SACC) can recur after removal of the primary tumor and treatment, where they can keep no clinical symptoms and dormant state for 10–15 years. NR2F1 has been demonstrated to regulate the tumor cell dormancy in various malignant tumors and has a potential impact on recurrence and metastasis of carcinoma. However, the role and significance of NR2F1 in SACC dormancy still remain unknown. Methods A total number of 59 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
(39 reference statements)
4
32
0
Order By: Relevance
“…Several studies have tried to define DCCs by biomarkers that associate to a dormant cell state, such as low levels of proliferation-associated protein Ki67 [14] in combination with lack of apoptotic markers such as TUNEL and M30 [7,15]. In addition, dormancy-regulating and -inducing signaling cascades have been identified, including members of the TGF-β family, reduced PI3K/AKT signaling, or p38 expression, which can serve as markers for DCCs [16,17].…”
Section: Emerging DCC Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tried to define DCCs by biomarkers that associate to a dormant cell state, such as low levels of proliferation-associated protein Ki67 [14] in combination with lack of apoptotic markers such as TUNEL and M30 [7,15]. In addition, dormancy-regulating and -inducing signaling cascades have been identified, including members of the TGF-β family, reduced PI3K/AKT signaling, or p38 expression, which can serve as markers for DCCs [16,17].…”
Section: Emerging DCC Biomarkersmentioning
confidence: 99%
“…To initiate a distant recurrence after treatment, these disseminated tumor cells therefore need to originate either from cells that escaped before local treatments by early dissemination, or from resistant cells that survived local or systemic treatment. Although disease relapse can occur shortly after treatment, many cases are described of metastatic disease occurring years or even decades after the first diagnosis and subsequent treatment, suggesting that cells initiating recurrence are often long-lived and able to reactivate proliferation after long latency periods (also referred to as clinical dormancy) [5][6][7]. Recurrent cancer has often acquired resistance mechanisms to the primary treatment, which in turn results in more aggressive tumor behavior and poor clinical outcome [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous ndings have demonstrated that atRA treatment can be used to induce dormancy in SACC cells, and its effects on cancer dormancy resulted directly from modulation of NR2F1 [15,16]. To further examine the molecular mechanism of tumor dormancy of SACC, atRA treated SACC-83 and the control cells were injected subcutaneously into nude mice, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…drived tumor dormancy in HNSCC and breast cancer [13,31]. Our previous study has demonstrated that atRA treatment could also drive tumor dormancy of SACC by upregulating NR2F1 [15]. Sosa et al…”
Section: Discussionmentioning
confidence: 96%
“…However, Abravanel and colleagues obtained different results when investigating the Notch family [181], likely because fine-tuning such an important pathway might cause dramatic differences, as is shown in other reports in the literature [176]. Another pathway that is still under investigation in this regard is the already cited SDF-1/CXCR4 pathway, which might partake in this process as well, although there is currently no consensus on the matter, and results seem to be pointing at different directions in different cancers [182][183][184][185].…”
Section: Tumour Cellular Dormancymentioning
confidence: 97%